Lamb wave-based air-coupled ultrasonic inspection technique for filament-wound composite pipes - Padiyar M, Janardhan; Balasubramaniam, K. (British Institute of Non-destructive Testing, 2014)
Filament-wound glass epoxy composite pipe-like structures require ultrasonic inspection in order to characterise any potential defects, such as those due to foreign inclusions and delaminations, so that defective as-manufactured components do not go into service. Current manual point-to-point contact or immersion-based ultrasonic inspections are effective but time consuming and expensive for large-diameter/long-span composite pipes. This work addresses the need for rapid defect inspection for these composite pipes. The detection of multiple artificial inclusions in the pipe using the A0 Lamb wave mode, generated and received using non-contact air-coupled ultrasonic transducers, is studied in this investigation. A two-step inspection technique is proposed. The first step consists of a single-sided global screening in the axial and radial directions of the pipe using the A0 mode for rapidly locating the defects. In the second step, a limited-area point-to-point air-coupled through-transmission inspection for sizing the defects is proposed. Lamb wave-based inspections are interpreted using a two-dimensional intensity profile (B-scans), which satisfactorily indicates the approximate locations of defective regions. The aim of this study is also to demonstrate a system using this proposed Lamb wave technique.
Keywords: Air-coupled ultrasonics; A0 Lamb mode; Non-contact inspection; Composite pipe